Human Nature from the Perspective of Islamic Educational Philosophy - Usiono, Usiono; Suhardi, Suhardi; Rudy erdianto (al-Afkar, Journal For Islamic Studies, 2025)
.  Understanding people is understanding yourself. The other individual is a representation of himself. However, within every human being, both as an individual and in a community, there is still a mystery that cannot be fully revealed. Humans are God's creation. who has a strategic role as a servant and at the same time caliph on earth. Humans are born in a state of purity, in the sense of fitrah. In an authentic hadith narrated by Bukhari and Muslim, it is stated that every child is born in a state of fitrah. It was his parents who allowed him to become a Jew, Christian, or Magian. This hadith implies that from birth, humans are equipped with various potentials called fitrah. Fitrah is an Arabic term which means a holy or good character, specially created by Allah swt. for humans as the main potential in the review of Islamic educational philosophy. Information related to humans is very much mentioned in the Qur'an as a reference and guide in everyday life to get the right path.